Warplanes - Graham, Ian, 1953- (Raintree, 2006)
Presents a short study of the world's greatest and fastest warplanes including the British Sopwith Camel and the U.S. P-51 Mustang from World Wars One and Two, and provides detailed facts on transport planes and helicopters, and much more.